2013
DOI: 10.1038/pr.2013.28
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopment after moderate hyperbilirubinemia at term

Abstract: Background:The aim of this work was to investigate in a prospective study whether moderate hyperbilirubinemia in healthy term neonates is associated with an increase of minor neurological dysfunction (MND) and behavioral problems up to 18 mo. Methods: We enrolled 43 healthy term infants with a bilirubin level ≥220 µmol/l (BILI group) at 72-96 h postnatally at the University Medical Center Groningen (UMCG), including eight referrals for hyperbilirubinemia. Seventy healthy term infants born at the UMCG with bili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Unconjugated bilirubin is toxic to the developing brain and may be elevated even in the presence of relatively low TB. Several studies have observed increased risk for motor and cognitive impairments following moderate TB levels in neonates [17], though the association between minor neurological/behavioral problems and moderate bilirubin exposure continues to be debated [18]. …”
Section: Severity Of Hyperbilirubinemiamentioning
confidence: 99%
“…Unconjugated bilirubin is toxic to the developing brain and may be elevated even in the presence of relatively low TB. Several studies have observed increased risk for motor and cognitive impairments following moderate TB levels in neonates [17], though the association between minor neurological/behavioral problems and moderate bilirubin exposure continues to be debated [18]. …”
Section: Severity Of Hyperbilirubinemiamentioning
confidence: 99%
“…1) and cerebellar roof nuclei, is an equally consistent feature of kernicterus [4,5]. With few exceptions [13,17], however, cerebellar lesions have not featured prominently in discussions of bilirubin-induced neurodevelopmental sequelae; their involvement, under-recognized perhaps because injury to other regions dominate the neurophenotype in classic kernicterus. As suggested by Koziol et al [13], and further detailed below, this may not be the case in BIND.…”
Section: Cerebellar Vulnerability To Bilirubin-induced Injurymentioning
confidence: 99%
“…As such, these conditions might also be manifestations of BIND [2,9,13]. However, as with subtle kernicterus, the linkage between hyperbilirubinemia and their genesis remains uncertain and a source of continued study and debate [1,2,6,[9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemolysis and liver hypoperfusion caused by ECMO techniques, abnormal liver function induced by cardiac failure and cardiac surgery before ECMO support may result in hyperbilirubinemia during ECMO support. Bilirubin at a high level can induce apoptosis, inflammation, and oxidative stress, which may lead to neural impairment , thrombocytopenia , and respiratory failure . The growing evidence has suggested that hyperbilirubinemia is related to poor prognosis of heart surgery and patients in ICU .…”
mentioning
confidence: 99%